Between Trust and Skepticism: Comparative Perceptions of ChatGPT in Academic Writing among EFL Learners in Indonesia and the Philippines - Antonio, Joemar; Ma'mun, Nadiah (Educalingua Journal, 2025)
This study investigates the comparative perceptions of Indonesian and Philippine EFL students regarding the use of ChatGPT in academic writing, focusing on the interplay between trust and skepticism. Employing a quantitative comparative research design with complementary qualitative inputs, data were collected from 232 university students using a structured questionnaire consisting of 20 closed-ended items analyzed quantitatively and two open-ended items analyzed qualitatively. Descriptive statistics and comparative analysis revealed that both groups perceived ChatGPT positively as a tool that improves writing quality, coherence, and confidence. However, students also expressed ethical concerns about plagiarism, overreliance, and authenticity. Filipino students tended to exhibit higher trust due to greater digital familiarity, while Indonesian students demonstrated stronger skepticism rooted in institutional and moral caution. The findings highlight the coexistence of trust and critical awareness, emphasizing the need for AI literacy education that integrates technological proficiency with ethical reflection. The study contributes to global discussions on AI-assisted writing by contextualizing the phenomenon within Southeast Asian educational settings.